Overview of Knowledge of Mothers Who Have New Babies Born 0 -7 Days About Maintenance Umbilical Cord Surgery at Partner Clinic St. Elisabeth College of Health Sciences Medan in 2025 - Kezia Ananta Fortuna Napitupulu; Desriati Sinaga (Journal Of Global Research Publications, 2025)
Newborns are a crucial transition period from life in the womb to life outside the womb. One important aspect of newborn care is hygienic and proper umbilical cord care, to prevent infections such as neonatal tetanus and accelerate the natural process of umbilical cord separation. Mothers' knowledge of umbilical cord care plays a crucial role in the success of such care. This study aims to determine the knowledge of mothers with babies aged 0–7 days regarding umbilical cord care at the Mitra Kerja Clinic of the Santa Elisabeth Health Sciences College in Medan. This study used a quantitative descriptive design with a purposive sampling technique, with 30 respondents. Data were collected through questionnaires and analyzed univariately. The results showed that most mothers had sufficient knowledge (50%), good (36.7%), and poor (13.3%). The majority of respondents were aged 20–35 years (96.7%), <20 years (3.3%), primigravida (56.7%), multigravida (43.3%) and had a high school education (70%), bachelor's degree (16.7%), and diploma (13.3%). Conclusion: Most mothers have sufficient knowledge about umbilical cord care. It is recommended that clinics conduct regular outreach sessions to improve mothers' understanding, and that further research be conducted by adding variables such as occupation and source of information